HUBUNGAN PENGETAHUAN GIZI ORANGTUA DAN PENDAPATAN ORANGTUA DENGAN KEPATUHAN ORANGTUA DALAM PENERAPAN DIET AUTIS PADA ANAK AUTIS DI SLB AUTIS LABORATORIUM UNIVERSITAS NEGERI MALANG - Poncowuri Handayani; Mazarina Devi; Agung Kurniawan (Preventia : The Indonesian Journal of Public Health, 2019)
Abstract: Autism is a behavioral deviation syndrome in children that involves sensory systems, communication skills, and socialization skills in community. Parental obedience in applying the diet should be consistent in order to reduce symptoms are undergone by children with autism. This study aims to determine the relationship between parental nutrition knowledge and parental income to parent’s obedience of complience in the application of autism diet in children with autism in the SLB Autis Laboratorium Malang State University. The type of this research is quantitative research with cross sectional study design. Parental knowledge was measured from a knowledge questionnaire, and income was measured by the per-capita income category per month and parental compliance was measured from Food Frequency Questionare (FFQ). The results showed that there was a significant correlation between parent’s nutritional knowledge and parent’s obedience to the application of the autism diet at SLB Autis Laboratorium Malang State University (p = 0,004) and there was a significant correlation between parent’s income with parent’s obedience to the application of the autism diet at SLB Autis Laboratorium Malang State University (p = 0,020). Suggestions for the next research to conduct more detailed research about per capita income of family by considering another factor.Keywords: knowledge, income, obedience, autism dietAbstrak: Autisme adalah suatu sindroma penyimpangan perilaku pada anak yang melibatkan sistem sensoris, kemampuan komunikasi, serta kemampuan sosialisasi dimasyarakat. Kepatuhan orang tua dalam menerapkan diet harus konsisten agar dapat mengurangi gejala yang dialami oleh anak autis. Penelitian ini bertujuan untuk mengetahui hubungan pengetahuan gizi dan pendapatan orangtua terhadap kepatuhan orangtua dalam penerapan diet autis pada anak autis di SLB Autis Laboratorium Universitas Negeri Malang. Jenis penelitian ini adalah penelitian kuantitatif dengan rancangan penelitian cross sectional. Pengetahuan orangtua diukur dari kuesioner pengetahuan, dan pendapatan diukur berdasarkan kategori pendapatan perkapita keluarga perbulan dan kepatuhan orangtua diukur dari Food Frequency Questionare (FFQ). Hasil penelitian menunjukkan bahwa terdapat hubungan yang signifikan antara pengetahuan gizi orangtua dengan kepatuhan orangtua dalam penerapan diet autis di SLB Autis Laboratorium Universitas Negeri Malang (p=0,004) serta terdapat hubungan yang signifikan antara pendapatan orangtua dengan kepatuhan orangtua dalam penerapan diet autis di SLB Autis Laboratorium Universitas Negeri Malang (p=0,020).  Saran bagi peneliti selanjutnya agar melakukan penelitian lebih mendetail lagi mengenai pendapatan perkapita keluarga dan dengan melihat faktor lain. Kata kunci: pengetahuan, pendapatan, kepatuhan, diet autis